Legal Protection For The Public Regarding The Amount of Compensation In Land Acquisition Activities For Development In The Public Interest - Achmad Ady Shufi Dahlan; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2025)
This study discusses the legal protection for communities regarding the amount of compensation in land acquisition activities for public interest development, emphasizing the principle of proportional compensation. It asserts that compensation should align with the value of the land and must be adequate, ensuring that land rights holders who relinquish their land do not experience social or economic decline. According to Articles 17 and 18 of Presidential Regulation No. 36 of 2005, if there is a dispute over the compensation amount, land rights holders have the right to submit objections to the Regent/Mayor, Governor, or Minister of Home Affairs, along with an explanation and reasons for the objection. The process of determining compensation should begin with deliberations, ensuring a fair and balanced resolution. This study concludes that the mechanism for providing compensation must prioritize deliberation, taking into account various factors, including social, cultural, legal, humanitarian, economic, and political aspects. These considerations ensure that the compensation process is not only fair and equitable but also respects the rights and dignity of the affected landholders, contributing to social harmony and public trust in the land acquisition process. This research provides valuable insights for policymakers and stakeholders involved in land acquisition for public development projects, ensuring that legal protections are in place to safeguard the interests of affected communities.